Edukasi Penerapan Komunikasi Kesehatan Dalam Upaya Penurunan Aki Dan Akb Pada Ibu-Ibu RT 011 Desa Tinggede Kecamatan Marawola Kabupaten Sigi - Rahmarini, Giska Mala; Ningsih, Fitriani Puspa; Haidar, Nur; Yahya, Rizki Ahmad; Kristian, Chandra (Journal Of Human And Education (JAHE), 2024)
Every pregnancy has a chance of an undesirable emergency situation in the future, namely the possibility of obstetric complications during childbirth that can cause death, pain, disability, discomfort or dissatisfaction (5 K) in the mother and or baby (Rohjati, 2013). (5 K) to the mother and/or baby (Rohjati, 2011). The role of health workers in the reduction of MMR and IMR, among others, is to provide continuous services focusing on aspects of prevention through health education and counseling, health promotion, normal childbirth assistance based on partnerships and empowerment of women, as well as conducting early detection. and women's empowerment as well as conducting early detection in cases of referral cases. Currently, reducing MMR and Infant Mortality Rate (IMR) is still a priority for health programs in Indonesia. priority health program in Indonesia. Midwives as midwifery care providers have a strategic position to play a role in accelerating the reduction of MMR and IMR. strategic position to play a role in accelerating efforts to reduce MMR and IMR. 2. A new paradigm in efforts to reduce maternal, infant, and child mortality rates, namely with continuous care. Continuous care is provided so that the incidence of MMR and IMR can be reduced because complications during pregnancy until the postpartum period are detected as early as possible. In this case, of course, the active role of In this case, of course, the active role of health workers is needed related to information information that can help prospective mothers and pregnant women themselves related to things that need to be considered during pregnancy until the ostpartum period. things that need to be considered in pregnancy or What preparations are needed for prospective mothers.